Valence and conduction band edges of selenide and sulfide-based kesterites—a study by x-ray based spectroscopy and ab initio theory. (20th September 2017) - Olar, Tetiana; Manoharan, Archana; Draxl, Claudia; Calvet, Wolfram; Ümsur, Bünyamin; Parvan, Vladimir; Chacko, Binoy; Xie, Haibing; Saucedo, Edgardo; Elisa Valle-Rios, Laura; Neldner, Kai; Schorr, Susan; et al.
Abstract: Thin film solar cells based on the kesterite material with the general composition Cu2 ZnSn(Se, S)4 can be a substitute for the more common chalcopyrites (Cu(In, Ga)(Se, S)2 ) with a similar band gap range. When replacing the anion sulfide with selenide, the optical band gap of kesterite changes from 1.5 to 1 eV. Here we report on a study of the valence band maximum and conduction band minimum energies of kesterites with either S or Se as the anion. Knowing these positions is crucial for the design of solar cells in order to match the bands of the absorber material with those of the subsequent functional layers like buffer or window layer. Their relative positions were studied using photoelectron spectroscopy of the valence band edge and x-ray absorption spectroscopy of the cations Cu, Zn, and Sn, respectively. The experimental results are interpreted and confirmed in terms of calculations based on density-functional theory and the GW approach of the many-body theory.